INVESTMENT CLIMATE IN RUSSIA: ANALYSIS OF EVALUATIONS OF INTERNATIONAL EXPERT ORGANIZATIONS AND RATING AGENCIES AT THE PRESENT STAGE - J. Lysenko; J. Konopleva (Вестник Северо-Кавказского федерального университета, 2022)
In this article the position of Russia is analyzed in the ratings of international organizations studying various aspects of the investment attraction of countries. The features of the investment climate in Russia were also considered, the constituent entities of the Federation were divided by the investment climate, the sectors that were most attractive for investment were identified, the indicators that were taken into account when setting a general assessment of the state's investment attractiveness in international ratings were identified. In addition, we considered factors that play a negative role in shaping the country's investment attractiveness from the point of view offoreign investors, and also we are developed recommendations for improving the investment climate in the Russian Federation.